2003
DOI: 10.1038/sj.modpathol.3800027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of MUC4 immunostaining in distinguishing epithelial mesothelioma and lung adenocarcinoma

Abstract: The distinction between pleural malignant mesothelioma and pleural infiltration by adenocarcinomas has complex therapeutic and medicolegal implications. Although the panel of adenocarcinoma-associated antibodies and one or two mesothelioma markers is useful in this purpose, most of these antibodies are not totally specific. We determined the diagnostic value of MUC4 immunostaining in this issue. MUC4 gene expression was also studied by in situ hybridization and RT-PCR. MUC4 is a membrane-bound mucin that has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Further research is, therefore, necessary to establish the clinical role of MUC4 in ovarian cancer. The significantly higher expression level of MUC4 in OC/PPC compared with DMPM is in agreement with the role of this molecule in differentiating lung adenocarcinoma from pleural mesothelioma (30). It is noteworthy that MUC4 is transactivated by PEA3 (31), a member of the Ets transcription factor family whose expression levels correlate with poor survival in patients with OC/PPC effusions (32).…”
Section: Discussionsupporting
confidence: 67%
“…Further research is, therefore, necessary to establish the clinical role of MUC4 in ovarian cancer. The significantly higher expression level of MUC4 in OC/PPC compared with DMPM is in agreement with the role of this molecule in differentiating lung adenocarcinoma from pleural mesothelioma (30). It is noteworthy that MUC4 is transactivated by PEA3 (31), a member of the Ets transcription factor family whose expression levels correlate with poor survival in patients with OC/PPC effusions (32).…”
Section: Discussionsupporting
confidence: 67%
“…4), in others (invasive ductal carcinoma of the pancreas, intrahepatic cholangiocarcinoma, and extrahepatic bile duct carcinoma), it was related to a poor clinical outcome (5-7). Another important aspect of MUC4 was recognized in distinguishing epithelial mesothelioma from invading lung adenocarcinoma (8). The distinction between the two malignancies is complicated due to the wide range of growth pattern of mesothelioma, a mesenchymally derived cancer with epithelial, fibrous, or mixed morphologic features.…”
Section: Muc4 In Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…The distinction between the two malignancies is complicated due to the wide range of growth pattern of mesothelioma, a mesenchymally derived cancer with epithelial, fibrous, or mixed morphologic features. Immunohistochemical analysis showed that MUC4 is overexpressed in lung adenocarcinoma and is useful in distinguishing lung adenocarcinoma from malignant mesothelioma, with 91.4% sensitivity and 100% specificity (8).…”
Section: Muc4 In Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…MUC4 is a large membrane-anchored glycoprotein that is aberrantly expressed in many cancers (12)(13)(14)(15)(16)(17)(18). Its expression is undetectable in the normal pancreas but increases progressively in pancreatic intraepithelial neoplasia (19,20) and is strongly expressed in PC (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%